2003
DOI: 10.4049/jimmunol.171.10.5107
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Thiols Contribute to Th2 Function via a Positive Role in IL-4 Production

Abstract: A number of lung diseases, including many interstitial lung diseases and HIV infection, are associated with decreases in intracellular thiols. Altered Th1/Th2 T cell balance has also been associated with disease progression in many of the same diseases. IFN-γ and IL-4 are critical effector cytokines of Th1 and Th2 cells, respectively. To determine the effect of thiols on the production of IFN-γ and IL-4 by splenocytes, cells were incubated in the presence and the absence of N-acetylcysteine (NAC) and stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…However, others reported that cytokine production by splenocytes of BALB/c mice was skewed towards a Th2 pattern when NAC was added in vitro [19]. In this study, we have shown that NAC enhances Th1 responses of NOD splenocytes in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…However, others reported that cytokine production by splenocytes of BALB/c mice was skewed towards a Th2 pattern when NAC was added in vitro [19]. In this study, we have shown that NAC enhances Th1 responses of NOD splenocytes in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…Some groups reported that low intracellular glutathione levels in murine APC or oxidative stress in human PBMC, respectively, promote the differentiation toward a Th2 phenotype (44,45). However, there are also reports suggesting that augmenting the intracellular thiol pool in mouse splenocytes with N-acetylcysteine blocked the induction of IFN-␥ and instead promoted IL-4 production and Th2 differentiation (46). This is consistent with our results showing that a more reduced milieu in APC due to the Ncf1 mutation mediated lack of ROS induces a more pronounced Th2 environment.…”
Section: Discussionmentioning
confidence: 95%
“…It has generally been accepted that a Th1/Th2 imbalance underlies various immune diseases. In HIV-infected patients and LP-BM5-infected mice, T-cell proliferation and Th1 cytokine (IL-2 and IFN-␥) production have been reported to decline, while Th2 cytokine (IL-4, IL-5, IL-6, and IL-10) and immunoglobulin production increase (4,5,10,12,26,34,45,49,57).…”
Section: Vol 80 2006 Cd4 T Cells In the Pathogenesis Of Murine Aidsmentioning
confidence: 99%
“…Th1 cells are involved in the pathogenesis of several organ-specific autoimmune disorders. In contrast, allergen-specific Th2 responses may be critical for atopic disorders in genetically susceptible individuals, and skewing to a Th2 response in certain infections diseases, such as leishmaniasis, leprosy, and others, results in a lack of clearance of the causative microbe and consequently in enhanced microbial and/or immunological pathology (4,34,45,57).…”
mentioning
confidence: 99%
See 1 more Smart Citation